Soil Microbial Diversity across Different Land-Use Types Using a Metagenomic Approach - Kasmawati Kasmawati (SEAN Institute, 2026)
The conversion of natural forests into agricultural land and monoculture plantations is a major driver of soil biodiversity loss in tropical regions, including Sumatra. Soil microorganisms are essential for nutrient cycling, organic matter decomposition, and soil fertility, yet their responses to land-use change remain insufficiently understood. This study analyzed the diversity and composition of soil microbial communities across four land-use types: natural forest, secondary forest/agroforestry, oil palm monoculture, and intensive agriculture. A quantitative comparative design was applied using 20 topsoil samples (0–20 cm). Microbial communities were characterized through Illumina-based 16S rRNA gene sequencing, followed by bioinformatic analysis in QIIME2 and statistical evaluation using one-way ANOVA and Principal Coordinate Analysis (PCoA). Microbial diversity declined significantly with increasing land-use intensity, with the Shannon index decreasing from 6.42 ± 0.21 in natural forest to 4.67 ± 0.19 in intensive agriculture (F = 18.7; *p* < 0.001). Taxa richness also decreased, accompanied by a shift in dominant phyla from Acidobacteria and Chloroflexi to Proteobacteria and Firmicutes. Soil organic carbon and total nitrogen were positively associated with microbial diversity. These findings demonstrate that land-use intensification reduces soil microbial biodiversity and highlight the importance of conserving natural vegetation and promoting agroforestry to sustain soil ecosystem functions.